Improve Student Skills in Read Understanding Text Explanation with Using the SQ3R Method - R, Delina; Mahendra, Hatma Heris; Nurani, Riga Zahara (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
The research has problem less reading comprehension ability explanation text in class IV. This research aims to increase reading comprehension ability using SQ3R in text explanation at IV class SDN Nantang. The researcher uses classroom action research. The result shows the use of SQ3R can increase reading comprehension ability in text explanation. Pre-test shows average scores are 45,83 with 27% complete and 73% incomplete. Cycle I with average scores are 75,67% with 60% complete and 40% incomplete and cycle II average scores 87,83 with 90% complete and 10% incomplete. The result of average is 42.  Reading comprehension ability is 53%. Based on the increase in pre-test until cycle I and cycle II, the conclusion is SQ3R can increase reading comprehension ability in text explanation at IV class SDN Nantang sub-district Cigalontang regency Tasikmalaya period 2020/2021